Entrepreneurs, Managers and Inequality - Sang Yoon Tim Lee (University of Mannheim, Department of Economics, 2012)
Since the 1980s, the U.S. income distribution has become considerably more concentrated toward the top while the wealth distribution has not. I argue that this can be accounted for by occupational shifts caused by the decline in tax progressivity. To show this, I construct a dynamic general equilibrium model of occupational choice which distinguishes between entrepreneurs, who run their own firms, and managers, who run publicly owned firms. Collateral constraints induce entrepreneurs to hold more wealth, while managers earn higher wages as a result of competitive assignments to firms. Feeding observed tax policy changes from 1970 to 2000 into the model, I find that (i) less progressive taxation increases the relative mass of managers in equilibrium, and explains approximately 30% of the observed increase in the concentrations of earnings and income without increasing that of wealth, and (ii) reverting to historical tax policies has only a negligible impact on consumption equivalent welfare.
urn:nbn:de:bsz:180-madoc-324356
Keywords: C68; E21; E62; J3; 330